Populism, Music and the Media. The Sanremo Festival and the Circulation of Populist Discourses - Magaudda, Paolo (PARTECIPAZIONE E CONFLITTO, 2020)
The article has the purpose of expanding the study of the relationship between music and populism in two directions. On a more theoretical level, the article aims at establishing further interconnections between political science, cultural sociology and media studies. On an empirical ground, a primary aim is that of presenting a distinctive case, able to offer an example of how populist discourses could emerge and circulate in relation with music phenomena; this empirical case is represented by the public controversy, anchored on populist references, emerged in Italy during the 2019 Sanremo festival, the most important musical event of the country. What emerges from the analysis is that the circulation of populist discourses in society requires a renewed theoretical sensibility, more able to intercept the role of aesthetic, cultural and symbolic phenomena, as well as a distinctive focus the role digital media technologies in reshaping the collective possibilities to articulate social and political identities.